Analisis Saluran Drainase di Pusat Kota Jepara dengan Program EPA SWMM 5.1 dan HEC RAS 4.1.0 - Shiska Fauziah; Slamet Imam Wahyudi; Hermin Poedjiastoeti (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2022)
From land value data sourced from the Central Bureau of Statistics of Jepara Regency that in Panggang Village, Jepara District, the transfer of land use for buildings is very high, which shows a percentage of 70.98%, therefore resulting in an open area in Jepara Regency for rainwater infiltration, especially in the main route segment is reduced, resulting in flooding and puddles in the city center location. Floods that occur are 40 cm to 80 cm high when it rains in the urban center area, there are several inundation points in the Jepara square, Kartini street, and Jepara's Chinatown area, and several other roads. The channel in Panggang Village is one of the infrastructures that supports the functioning of an urban system in Jepara City. In the existing channel along the Wiso River area, inundation often occurs every rainy season, so it is necessary to conduct a study to analyze the capacity of the drainage channel. The data used in planning is secondary data. Secondary data was obtained from the schematic drawing of the drainage channel and data regarding the dimensions of the channel and hydrological data. The hydrological and hydraulic data obtained were then analyzed to obtain the design discharge and drainage channel capacity. The design discharge is calculated using the rational method and the channel capacity is calculated using the HEC RAS ​​4.1.0 and EPA SWMM 5.1 software modeling. This study examines Drainage Channel Capacity Analysis to evaluate flooding based on the existing condition of drainage channels that affect the occurrence of flooding using HEC RAS ​​4.1.0 and EPA SWMM 5.1 software models. HEC RAS ​​4.1.0 software. Based on the results of hydrological analysis, the distributions chosen are Gumbel Type I Distribution and Log Pearson Distribution Type III. In the fit test, it was concluded that the Log Pearson Type III distribution method met the requirements because the Dmax value of -0.0202 was less than Do 0.41. and hydraulic analysis obtained by software HEC RAS ​​4.1.0 and EPA SWMM 5.1. at the 1 year return period there are 2 points that experience flooding and 4 points that are able to accommodate flood discharge. The flood points are scattered in several areas in Panggang Village, namely Jl. RA. Kartini and Jl. Youth. In dealing with flooding, it is necessary to re-plan the drainage for the 10-year return period in order to create security and comfort for local residents.